2016
DOI: 10.5433/1679-0359.2016v37n4p2247
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nutritional potential of protodioscin and kinetics of degradation in Urochloa grasses

Abstract: This study aimed to evaluate the nutritional value of Urochloa exotic grasses to quantify aspects of antiquality and to identify their correlation with quality grasses. We evaluated the grasses U. humidicola cv. Comum, U. humidicola cv. BRS Tupi, U. decumbens cv. Basilisk, D70 U. decumbens and U. ruziziensis ecotype R124, and we grouped them into summer, autumn, winter and spring. We determined the chemical composition, in vitro digestibility, levels of protodioscin and cumulative gas production from the leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
3
8
0
Order By: Relevance
“…According to Van Soest (1994), that is explained by the decrease in cell content, whereas the high CP content at 14 days of age is related to the initial vegetative growth stage of the forage plant. The values found in the present study at 30 days (11.74 g/100 g) match those by Leal et al (2016), who assessed the nutritional value of BRS Tupi cut in 30-day intervals in summer, autumn, winter, and spring. Those authors reported CP contents of 8.79, 8.31, 8.71, and 10.6 g/100 g, respectively, i.e., higher age at cut led to lower CP contents.…”
Section: Age In Dayssupporting
confidence: 89%
See 2 more Smart Citations
“…According to Van Soest (1994), that is explained by the decrease in cell content, whereas the high CP content at 14 days of age is related to the initial vegetative growth stage of the forage plant. The values found in the present study at 30 days (11.74 g/100 g) match those by Leal et al (2016), who assessed the nutritional value of BRS Tupi cut in 30-day intervals in summer, autumn, winter, and spring. Those authors reported CP contents of 8.79, 8.31, 8.71, and 10.6 g/100 g, respectively, i.e., higher age at cut led to lower CP contents.…”
Section: Age In Dayssupporting
confidence: 89%
“…NDF is a major parameter in defining forage quality and limits the intake capacity of animals (Costa et al, 2007). Hence, forage plants harvested at more advanced ages will be less consumed and digestible by animals (Jung & Allen, 1995;Leal et al, 2016). Age in days growth stage of the forage plant.…”
Section: Age In Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of low productivity rates, the Brazilian commercial cattle herd amounts to 209,541,109 units. It has been estimated that 89% are raised exclusively on pasture in native or cultivated pasturelands covering some 172 million ha and approximately 85% of this area is pasture of the genus Urochloa (Leal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The content of protodioscin-the main saponin associated with intoxication and used as an indicator of photosensitization in animals (Lelis et al, 2018)-in the cultivars was low when compared with those described in studies with cultivars of the genus Brachiaria (Faccin et al, 2014;Porto et al, 2013;Leal et al, 2016Leal et al, , 2020. In Brachiaria spp., Melo et al (2018) found that protodioscin levels between 3 and 13 g/kg DM caused intoxication in lactating lambs.…”
Section: Chemical Compositionmentioning
confidence: 83%